The secret language of color Science,nature,history,culture,beauty of red,orange,yellow,green,blue & violet - Eckstut, Joann; Eckstut, Joann (New York Blackdog leventhal, 2013)
Color is a basic human need:like fire and water, a raw material, indispensable to life